2014
DOI: 10.2196/jmir.3147
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Intervention Programs for Depression: A Scoping Review and Evaluation

Abstract: BackgroundAlthough depression is known to affect millions of people worldwide, individuals seeking aid from qualified health care professionals are faced with a number of barriers to treatment including a lack of treatment resources, limited number of qualified service providers, stigma associated with diagnosis and treatment, prolonged wait times, cost, and barriers to accessibility such as transportation and clinic locations. The delivery of depression interventions through the Internet may provide a practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
112
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(122 citation statements)
references
References 51 publications
7
112
0
3
Order By: Relevance
“…Four interventions had a CBT only approach. CBT is the most commonly used approach in web-based depression interventions [49][50][51] and with a guided self-help methodology have shown the same effects when compared directly to face-to-face CBT therapy [28]. However, all interventions are multicomponent with a number of hypothesized mechanisms (e.g.…”
Section: Discussion Principal Results and Comparison With Previous Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Four interventions had a CBT only approach. CBT is the most commonly used approach in web-based depression interventions [49][50][51] and with a guided self-help methodology have shown the same effects when compared directly to face-to-face CBT therapy [28]. However, all interventions are multicomponent with a number of hypothesized mechanisms (e.g.…”
Section: Discussion Principal Results and Comparison With Previous Workmentioning
confidence: 99%
“…This is a reflection of the small number of web-based depression interventions that offer this kind of support [50]. A meta-analysis on web-based interventions for diabetes management showed that online peer support was a successful approach [59], but in interventions for depression the evidence is limited and show inconsistent findings [65].…”
Section: Discussion Principal Results and Comparison With Previous Workmentioning
confidence: 99%
See 3 more Smart Citations